2002
DOI: 10.1590/s0004-282x2002000300013
|View full text |Cite
|
Sign up to set email alerts
|

Eficácia de três drogas sobre a aura migranosa: um estudo randomizado placebo controlado

Abstract: RESUMO -A despeito da enorme quantidade de pesquisas referentes à classificação, epidemiologia, diagnóstico, fisiopatologia e tratamento da migrânea, a aura migranosa permanece bem menos estudada. O objetivo do presente estudo é, portanto, verificar a evolução da aura em pacientes submetidos a placebo e a três diferentes drogas disponíveis em unidades públicas de saúde brasileiras. Foram estudados 86 pacientes em vigência de crise de migrânea com aura, apresentando aura no momento da randomização. Após a rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…All of them were intention-to-treat randomized controlled trials with a parallel-group design and were classified as B according to the Cochrane Handbook criteria (13) . According to Jadad scale, one 23 was classified as 5, and the other three [24][25][26] as 4. Only one included trial 23 reported any dropouts: 4 patients (1 randomized to dipyrone 0.5 g and 3 randomized to dipyrone 1 g) were excluded from the analysis for failing to return their study diaries.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…All of them were intention-to-treat randomized controlled trials with a parallel-group design and were classified as B according to the Cochrane Handbook criteria (13) . According to Jadad scale, one 23 was classified as 5, and the other three [24][25][26] as 4. Only one included trial 23 reported any dropouts: 4 patients (1 randomized to dipyrone 0.5 g and 3 randomized to dipyrone 1 g) were excluded from the analysis for failing to return their study diaries.…”
Section: Resultsmentioning
confidence: 99%
“…Three of these studies were performed in the same centers (two public health units) in Brazil by the same group of authors [24][25][26] . One trial 23 included 31 participating centers, and subjects were not hospitalized.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations